Assessment of contact parameters of soft splined hemispherical finger-tip pressed against a concave profile. (22nd June 2018) - Yuvaraj, S; Malayalamurthi, R; Gokulprasath, S; Venkatesh Raja, K
Abstract: Soft material contact analysis plays an important role in the theory of non-linear contact mechanics on both macro and micro scales. Understanding the conforming nature of soft materials with various contact destinations is of considerable interest which involves design of mechanical components involving soft materials. This work presents a FEM based investigation on the contact parameters of a soft splined hemispherical finger-tip pressed against a rigid curved profile. The contact parameters viz., contact pressure, contact radius and vertical deformation for different loads are estimated by FEM based axis-symmetric model. The geometry of the splined portion on soft finger-tip is specified by the length, width and depth. The load-contact relationship for different splined profiles was completed and discussed. From the results, it is observed that the magnitude of vertical depression of splined fingertip is always greater than the normal rigid fingertip. The underlying physics behind this phenomenon is due to large lateral deformation in the splined profile. Then the magnitude of contact radius decreases with the increase in length of the spline. Also, the width of the spline plays an important role in the development of contact area. Moreover, additional grasping strength will be attained due to the vacuum generated in between the splines.